Degradable esophageal fistula plugging device

By adopting a multi-layer degradable degradable layer structure in the esophageal fistula occluder, using materials such as closed-cell aerogel and polylactic acid, better sealing effect and fistula jointing are achieved, and the existing technology is solved The problem of poor degradation of the occluder reduces complications and improves patient comfort.

CN119405374APending Publication Date: 2025-02-11THE FIRST AFFILIATED HOSPITAL OF GUANGZHOU MEDICAL UNIV (GUANGZHOU RESPIRATORY CENT)
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411334440.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing esophageal fistula occlusion devices have poor effect during the degradation process and lack practical degradable occlusion devices, resulting in poor sealing effect and poor fistula fit.

Method used

Using a multi-layer degradable degradation layer structure, the outer degradation material has a fast degradation rate, and the inner material supports the fistula position to form a bonding and sealing effect. Specifically, materials such as closed-cell aerogel and polylactic acid are used to achieve hierarchical degradation through gradient design.

Benefits of technology

A better sealing effect and fistula fit are achieved, reducing long-term complications of the occluder, promoting natural growth and development, improving patient comfort, and reducing metal sensitivity reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405374A_ABST
    Figure CN119405374A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of esophageal fistula plugging devices, and particularly relates to a degradable esophageal fistula plugging device. The invention provides a degradable esophageal fistula plugging device which is characterized in that the plugging device is provided with multiple degradable degradation layers, and the degradation speed of the degradable layers is increased from inside to outside. The plugging device has the advantages that the gradient degradable material is adopted, the effect of anastomosing a fistula is achieved through gradient degradation, and secondary trauma possibly caused to the position of the fistula is reduced; the spongy structure of the plugging device is prepared from aerogel, so that the overall weight of the plugging device is greatly reduced, and the plugging device is convenient to use; and 3, long-term complications can be reduced, namely, the aerogel can be finally absorbed by the body, so that the infection risk or other long-term complications caused by long-term existence of foreign matters can be reduced. And 4, the comfort level of the patient is improved: as time goes on, the degradable plugging device does not occupy space any more, and the comfort level of the patient is possibly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of esophageal fistula occluders, and in particular relates to a degradable esophageal fistula occluder. Background Art

[0002] For the more common fistulas, such as esophageal bronchial fistula, esophagogastric anastomotic fistula, residual gastric fistula, gastrointestinal anastomotic fistula, various intestinal fistulas, vesico-vaginal fistula, and rectovaginal fistula, blocking the fistula is an important measure to temporarily close the fistula, restore the continuity of the digestive tract, respiratory tract, urinary tract, etc., and prevent the contents from spilling out, thereby reducing the corrosion of the contents to the surrounding tissues and the loss of body fluids, as well as the resulting fatal complications such as infection and massive bleeding. Blocking the fistula also creates a relatively clean growth environment, which is conducive to the growth and healing of the tissue at the fistula, effectively shortens the treatment time, and can quickly restore the normal functions of the digestive tract, respiratory tract, urinary tract, etc. The commonly used methods of blocking fistulas are: for small slit fistulas, various medical glues and clamping methods are used through interventional approaches such as gastroenteroscopy, bronchoscopy or cystoscopy.

[0003] Existing esophageal fistula blocking devices generally use a woven fabric occluder made of a memory metal stent as a skeleton support, or block the fistula in the form of an airbag, while occluders made of degradable materials are generally more commonly used as occluders between the atrioventricular compartments. Currently, there is no more practical degradable occluding device for esophageal fistula.

[0004] According to the current design ideas, the degradable occluder is basically formed by using the braided structure of the memory metal stent. Such as Chinese patent publication numbers: CN110464403A, CN111920460A, CN118252554A, CN110432935A. The above occluder structures all use a braided structure to form a blocking structure, but there are still problems. First, the braided fabric of the occluder itself does not have memory function and elastic function, so more of them are mixed braided models. The so-called degradable occluder is only partially degradable rather than completely degradable, and some of them use a degradable skeleton support structure. Since the material itself is not metal, it is difficult to achieve the effect of elastic support.

[0005] Currently, for esophageal fistula occluders, the occlusion effect is closely related to the fit of the fistula opening. If the fistula opening does not fit well, or due to the degradation of the occluder itself, the occluder will be quickly deformed or damaged, resulting in poor occlusion effect. Summary of the invention

[0006] In order to avoid the problem of poor blocking effect caused by degradation of the occluder and the lack of degradable occluders in the technical field of esophageal fistula occluders, the present invention proposes a degradable esophageal fistula occluder, and the specific technical solution is as follows: The degradable esophageal fistula occluder comprises a multi-layered degradable layer, wherein the degradation speed of the degradable layer increases from the inside to the outside.

[0007] The core solution of the present invention is a multi-layered degradable layer, which can achieve dual goals at the same time. Goal 1: After the outer layer of degradable material is degraded, the inner layer of material can support the fistula position to achieve a blocking effect. Goal 2: The degradation rate of the outer layer of degradable material is fast, and after partial degradation of the outer layer of material, it can better form a shape that matches the fistula, forming a fitting blocking effect. Since the degradation rate of the degradable material is related to many other factors, the effect of adjusting the degradation rate can be achieved by adjusting the relevant factors, such as: molecular weight, crystallinity, ratio of stereoisomers, degree of branching, additives and other related factors. Furthermore, the degradable layer is provided by closed-cell aerogel. Aerogel is a porous material with extremely high porosity and extremely low density. The basic structure of aerogel is a continuous network composed of nanoscale particles or fibers, which are connected together by van der Waals forces or other forms of interaction to form a highly interconnected three-dimensional skeleton. This structure enables aerogel to have a very large specific surface area (usually more than several hundred square meters per gram), and the interior is filled with air, so it has a very low density. The pores in aerogel can be open or closed. The open-cell structure allows fluid to pass through, while the closed pores do not allow fluid to penetrate. The present invention adopts a closed-cell aerogel structure, and the closed-cell aerogel structure is set to better achieve degradation from the outside to the inside. The degradable occluders currently on the market use fibers or braids. After absorbing water, the entire braid is degraded as a whole. The morphology of the occluder during the degradation process is uncontrollable. The present invention uses a closed-cell aerogel structure to effectively avoid this.

[0008] Furthermore, the degradable layer is made of polylactic acid.

[0009] Polylactic acid (PLA) is a bio-based, degradable thermoplastic polymer. Due to its low cost and good degradation performance, it has shown broad application prospects in packaging, textiles, medical and other fields. Polylactic acid (PLA) is a high molecular polymer formed by polymerization of lactic acid monomers. Lactic acid has two optical isomers: L-lactic acid and D-lactic acid. Therefore, PLA can be a homopolymer of L-lactic acid, a homopolymer of D-lactic acid, or a copolymer of D-lactic acid and L-lactic acid. The present invention mainly uses polylactic acid or modifies it on polylactic acid.

[0010] Furthermore, the innermost layer of the occluder is a degradable memory foam layer, and the components of the degradable memory foam layer are palm oil polyol and polylactic acid, and the component ratio is 0.1-0.2:1 Palm oil polyol is a bio-based polyol, which is mainly prepared by chemical modification of natural palm oil. It is widely used in the production of polyurethane (the main raw material of memory foam, non-degradable) as an environmentally friendly material to replace traditional petroleum-based polyols. Palm oil polyol Palm oil polyol can improve the flexibility, durability and resistance of polylactic acid aerogel, give polylactic acid aerogel slow rebound performance, and play the role of supporting the overall shape of the occluder from the inside to the outside. Palm oil polyol, as a bio-based material, has better degradation performance and biocompatibility than petroleum-based polyols, but compared with polylactic acid, palm oil polyol modification makes the innermost layer of the occluder more durable and slow rebound elasticity, which are also the performance characteristics that meet the actual needs of the present invention. The slow rebound elasticity allows the occluder to be compressed in the release catheter, and can gradually return to its initial state after release, instead of being flattened in the catheter and unable to recover, then there is no blocking effect. The innermost layer is more durable, which allows the overall occluder to be maintained longer, and the degradation rate of the occluder decreases from the outside to the inside.

[0011] Furthermore, the outermost layer of the occluder is a fast degradation layer, and the components of the fast degradation layer are graphene oxide, polylactic acid, and a crosslinking agent. Graphene oxide is a derivative of graphene, which is a two-dimensional material prepared by chemical oxidation of graphite. Graphene oxide has unique physical and chemical properties and a wide range of potential applications. Graphene oxide is a single-layer or a few-layer graphene sheet, and its surface is rich in oxygen functional groups (such as hydroxyl, carboxyl, epoxy, etc.). These oxygen functional groups make graphene oxide hydrophilic. Through its hydrophilic characteristics, the modification of graphene oxide can further accelerate the degradation rate of the outermost layer of the occluder. At the same time, graphene oxide has certain antibacterial properties. The sharp edges of graphene oxide can penetrate the bacterial cell wall, causing the cell contents to leak, thereby killing bacteria. GO sheets can adhere to the surface of bacteria, interfere with the normal function of the cell membrane, and affect the metabolism of bacteria. When the occluder is initially released, it can be antibacterial to the fistula wound site, accelerate the healing function, and other functional characteristics.

[0012] Furthermore, the polylactic acid is a D,L-lactic acid copolymer with a degree of polymerization of 800-5000.

[0013] Since the degradation rate and physical properties of degradable materials are closely related to molecular weight, generally speaking, as the molecular weight increases, the tensile strength of polylactic acid will also increase. This is because a high molecular weight means a longer polymer chain, and the interaction between chains is stronger, so the material is stronger. Generally, polylactic acid with a lower molecular weight degrades faster. This is because a lower molecular weight means that it is easier to be hydrolyzed or enzymatically hydrolyzed, thereby breaking the polymer into small molecules and then being degraded by microorganisms. Taking into account the physical properties and degradation properties of polylactic acid, polylactic acid is selected as a D, L-lactic acid copolymer with a degree of polymerization of 900-5000 as the main material of the present invention. Generally speaking, the polylactic acid of the outermost degradation layer of the occluder has a degree of polymerization of 900, and the polylactic acid of the innermost degradation layer has a degree of polymerization of 5000.

[0014] Furthermore, the occluder is formed into a dumbbell shape on the outside, and a cavity is provided in the degradation layer.

[0015] The cavity setting reduces the weight of the occluder, facilitates compression before the occluder is released, and facilitates the rebound of the innermost layer of the occluder, thereby improving the rebound effect.

[0016] Furthermore, a reinforcement structure is arranged in the innermost layer of the degradation layer.

[0017] It should be noted that the multi-layered degradable layer of the present invention has a degradation rate that increases from the inside to the outside, which can be understood as a stepped multi-level structure, or a gradient functional material. The specific preparation process of the gradient functional material can be referred to in "Research on the Preparation and Application of Polylactic Acid Gradient Functional Materials" (Niu Ruiqin, Zou Hantao, Wu Qian, et al. Materials Guide, 2015, 29 (19): 128-134.) which mentions a large number of preparation methods such as temperature gradient field method, controlled reaction method, component dosage control method, dissolution and diffusion method, the purpose of which is to achieve a gradient continuous change in material properties from one end to the other. It can be understood that the occluder structure made of the gradient functional material is formed by many levels, which should also fall within the scope of protection of the present invention.

[0018] The gradient design of degradable materials achieves the effect of hierarchical degradation, which has good fistula adaptability and has the following advantages compared with the current memory metal occluder: 1. Reduce long-term complications: Since they are eventually absorbed by the body, they can reduce the risk of infection or other long-term complications caused by the long-term presence of foreign objects.

[0019] 2. Promote natural growth and development: For pediatric patients, biodegradable materials allow the heart structure to develop naturally as the child grows without being restricted by metal or plastic devices.

[0020] 3. Improve patient comfort: Over time, the degradable occluder no longer takes up space, which may improve patient comfort.

[0021] 4. Reduce metal sensitivity reactions: Some people may be allergic to the metal components in traditional occluders. Using biodegradable materials can avoid such allergic reactions.

[0022] 5. Use gradient degradable materials: Gradient degradation is used to achieve the effect of anastomosis of the fistula, reducing the possible secondary trauma to the fistula location.

[0023] 6. The sponge-like structure of the occluder is prepared by aerogel, which greatly reduces the overall weight of the occluder and has a very good use effect. The external pores of the aerogel are closed, which makes it have a good blocking effect.

[0024] 7. The present invention is mainly made of polylactic acid and its modified materials, which realizes the degradable function under the conditions of wound healing, reducing secondary trauma, anti-inflammatory and sterilization, and light weight, and has excellent practical value in the use scenario of esophageal fistula occluder. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a sample diagram of Example 1 of the present invention.

[0026] Figure 2 Schematic diagram of the internal structure of Example 1 of the present invention.

[0027] Figure 3 This is a schematic diagram of the compressed state in the catheter of Example 1 of the present invention.

[0028] Figure numerals: 1. Outermost layer, 2. Middle layer, 3. Innermost layer, 4. Reinforcement structure 1, 5. Reinforcement structure 2, 6. Reinforcement structure 3, 7. Reinforcement structure 4. DETAILED DESCRIPTION Example 1

[0029] like Figure 1 As shown, the occluder of the present invention is formed into a dumbbell shape. Figure 2 As shown, the multi-layered degradable layer provided in the present invention is a three-layer structure of the outermost layer 1, the middle layer 2, and the innermost layer 3 from the outside to the inside, and the three-layer structure is all provided by closed-cell aerogel. The specific preparation methods include: sol-gel method, freeze-drying method, carbon dioxide critical point drying method, normal pressure drying, and self-supporting gel method. Considering the time cost and economic cost, the normal pressure drying method is used for preparation, which includes the following steps: 1. Gel Preparation 1.1 Sol preparation: Dissolve the precursor (including other components including polylactic acid) in a solvent (such as water, alcohol, etc.), and add an appropriate amount of catalyst (such as acid or base) to promote hydrolysis and condensation reactions to form a uniform sol.

[0030] 1.2 Gel formation: Pour the sol into a mold and promote the formation of gel by standing or heating. The formation of gel can be observed by the naked eye.

[0031] 2. Natural aging: Leave the gel at room temperature for a period of time to naturally age in order to improve the structural stability of the gel.

[0032] 3. Vacuum drying: The gel was dried under negative pressure in a vacuum oven.

[0033] In this embodiment, the outermost layer 1 is made of graphene oxide, polylactic acid (polymerization degree 1000), and a cross-linking agent (polyethylene glycol), and the component ratio is: 1:24:0.2 In this embodiment, the middle layer 2 is made of: a copolymer of D-lactic acid and L-lactic acid (polymerization degree 1200) In this embodiment, the innermost layer 3 is made of: a degradable memory foam layer, the components of the degradable memory foam layer are palm oil polyol and polylactic acid (polymerization degree 2500), and the component ratio is 0.1:1 like Figure 2 As shown, the outermost layer 1, the middle layer 2, and the innermost layer 3 in this embodiment are prepared by a sleeve structure.

[0034] like Figure 2 As shown, the innermost layer 3 is provided with reinforcement structures in some specific structures, such as reinforcement structure 1 4, reinforcement structure 2 5, reinforcement structure 3 6, reinforcement structure 4 7, to improve the structural strength of the innermost layer, combined with Figure 3 It can be seen that when the occluder is still inside the catheter, the occluder is in the shape of a strip, and the innermost layer 3 has a large stress at the positions of the reinforcement structure 1 4, the reinforcement structure 2 5, the reinforcement structure 3 6, and the reinforcement structure 4 7. When the occluder is released, it can rebound well to Figure 2 The shape of the occluder structure. Example 2

[0035] The difference between Example 2 and Example 1 is that the components of the outermost layer, the middle layer, and the innermost layer are slightly different, and the effects achieved are similar.

[0036] In this embodiment, the outermost layer 1 is made of graphene oxide, polylactic acid (polymerization degree 1200), and a cross-linking agent (polyethylene glycol), and the component ratio is 1:24:0.15.

[0037] In this embodiment, the middle layer 2 is made of a copolymer of D-lactic acid and L-lactic acid (degree of polymerization: 1500).

[0038] In this embodiment, the innermost layer 3 is made of: a degradable memory foam layer, the components of the degradable memory foam layer are palm oil polyol and polylactic acid (degree of polymerization 2500), and the component ratio is 0.12:1. Example 3

[0039] The difference between Example 2 and Example 1 is that the components of the outermost layer, the middle layer, and the innermost layer are slightly different, and the effects achieved are similar.

[0040] In this embodiment, the outermost layer 1 is made of graphene oxide, polylactic acid (polymerization degree 800), and a cross-linking agent (polyethylene glycol), and the component ratio is 1:50:0.3.

[0041] In this embodiment, the middle layer 2 is made of a copolymer of D-lactic acid and L-lactic acid (degree of polymerization: 1200).

[0042] In this embodiment, the innermost layer 3 is made of: a degradable memory foam layer, the components of the degradable memory foam layer are palm oil polyol and polylactic acid (polymerization degree 5000), and the component ratio is 0.2:1.

[0043] It should be noted that the present invention adopts a closed-cell aerogel structure, which is a more preferred implementation structure. Of course, an open-cell aerogel structure also falls within the protection scope of the present invention, and a porous material structure obtained by physical foaming or chemical foaming methods also falls within the protection scope of the present invention.

[0044] It should be noted that although the embodiment of the present invention only provides a three-layer structure of the occluder, namely, the outermost layer, the middle layer, and the innermost layer, those skilled in the art can make further improvements based on the understanding of the core of the present invention, such as providing more middle layers in the outermost layer and the innermost layer to achieve a better gradient function effect. It should be understood that the technical solutions formed by the equivalent replacement or equivalent transformation all fall within the scope of protection claimed by the present invention.

[0045] In addition, in this specific embodiment, if the connection or fixing method between components is not particularly described, the connection or fixing method can be through conventional one-piece molding or the like in the prior art, and therefore, it will not be described in detail in this embodiment.

[0046] Of course, the above are only typical examples of the present invention. In addition, the present invention may also have many other specific implementations. All technical solutions formed by equivalent replacement or equivalent transformation fall within the scope of protection required by the present invention.

Claims

1. A degradable esophageal fistula occluder, characterized in that: The invention comprises a multi-layered degradable layer, wherein the degradation speed of the degradable layer increases from the inside to the outside.

2. The degradable esophageal fistula occluder according to claim 1, characterized in that: The degradable layer is provided by closed-cell aerogel.

3. The degradable esophageal fistula occluder according to claim 1, characterized in that: The degradable layer is made of polylactic acid.

4. The degradable esophageal fistula occluder according to claim 1, characterized in that: The innermost layer of the occluder is a degradable memory foam layer, and the components of the degradable memory foam layer are palm oil polyol and polylactic acid, and the component ratio is 0.1-0.2:

1.

5. The degradable esophageal fistula occluder according to claim 1, characterized in that: The outermost layer of the occluder is a fast degradation layer, and the components of the fast degradation layer include graphene oxide, polylactic acid, and a cross-linking agent.

6. The degradable esophageal fistula occluder according to claim 4-5, characterized in that: The polylactic acid is a D, L-lactic acid copolymer with a polymerization degree of 800-5000.

7. The degradable esophageal fistula occluder according to claim 1, characterized in that: The occluder is formed into a dumbbell shape on the outside, and a cavity is arranged in the degradation layer.

8. The degradable esophageal fistula occluder according to claim 7, characterized in that: A reinforcing structure is arranged in the innermost layer of the degradation layer.

Citation Information

Patent Citations

  • Degradable plugging device and preparation method thereof

    CN110432935A

  • Absorbable plugging device

    CN110464403A

  • Mixed-weaving plugging device

    CN111920460A

  • Absorbable plugging device

    CN118252554A

  • Multilayer degradable tube and stent and preparation method thereof

    CN105477690A